Prevalence and pre-disposing factors of Helicobacter pylori among patients with gastro-intestinal symptoms attending Mulago Hospital, Kampala, Uganda - Racheal Twikirize; Phillip Wanduru; Tumwine Gabriel; David Musoke (PLoS ONE, 2026)
Background Comprehensive data on the prevalence of Helicobacter pylori infection and its predisposing factors among patients with gastrointestinal symptoms remain limited. Generating this evidence would help inform clinical management and improve antibiotic stewardship. H. pylori infection affects a substantial proportion of the global population, with prevalence varying widely across regions. In Uganda, previous studies have documented the presence of H. pylori infection. However, data specific to symptomatic patients are scarce. This study therefore aimed to determine the prevalence of H. pylori infection and predisposing factors among patients with gastrointestinal symptoms attending Mulago National Referral Hospital in Kampala, Uganda. Methods A cross-sectional study was conducted among 353 patients with gastrointestinal symptoms attending Mulago Hospital. Data on socio-demographic characteristics, lifestyle and dietary habits, and medical history were collected using a semi-structured questionnaire. H. pylori infection status was determined using stool antigen tests. Proportions were used to determine the prevalence of H. pylori, and predisposing factors analyzed using STATA version 14 software by performing bivariate and multivariable analyses. Results Among the 353 participants, majority were between 16 and 35 years old (69%), female (58%), and residing in peri-urban areas (74%). The prevalence of H. pylori infection in this population was 308 (87.3%). Multivariable analysis showed that H. pylori infection was significantly associated with having more than five income dependents (aPRR = 1.104, 95% CI: 1.025–1.189, p = 0.008), a history of previous H. pylori treatment (aPRR = 3.459, 95% CI: 2.138–5.595, p < 0.001), and a family history of H. pylori infection or gastrointestinal ulcers (aPRR = 1.135, 95% CI: 1.055–1.221, p = 0.001). Conclusion This study demonstrated a high prevalence of Helicobacter pylori infection among patients presenting with gastrointestinal symptoms, with nearly nine out of ten individuals testing positive. The high burden observed suggests that routine screening for H. pylori , or carefully guided empirical treatment, may be clinically justified in symptomatic patients. These findings underscore the need for integrated clinical and public health strategies to improve diagnosis, treatment, and prevention of H. pylori infection in this setting.